The consequences of family breakdown in post-independence Nigeria : a case study of Borno state - Usman, Hamidu Bagwan (1989)
This is a study of the social and legal consequences of family breakdown in Nigeria as a whole but with specific reference to Borno State. It examines the effects of family breakdown on the husband and wife or wives and their children under the General Laws, Customary Law and Islamic Law of the people of Maidugurij Biu, and Gwoza areas of Borno State. The study covers the post-Independence period-i. e from 1960 to today. The aim of the study is to show how the social and economic changes in society affect the family at divorce. Although social change is part of any society, this study shows that the formal law on family breakdown and its consequences have not kept pace with social change, and that the dichotomy between state law and customary or Islamic law on family breakdown exists only in court. Thus the authority of the extended family, and within it, the dominance of men over womens, has not been specifically disturbed by the increasing Westernisation and rural-urban migration that has taken place since Independence. It is under this situation that the rights of women, property settlement on divorce, maintenances, and custody of children, as the main indicators of the consequences of family breakdown in any society has to be gauged. The role of the law and the state is also discussed. We argue that all the post-Colonial governments in the Federation were responsible for the present deplorable condition of victims of family breakdown not only in Borno State but throughout the country. Thus there has been no state-provided Social welfare to cater for deserted wivest children, and destitutes despite the ever increasing needs of such persons in a society that is rapidly changing. It is within this context that the effect of family breakdown on the people of Borno State is examined. The study argues that the various state authorities in Nigeria tend to abandon their responsibility to the family to the traditional customary institutions, such as the extended familyf which are now incapable of meeting the needs of victims of family breakdown. Moreoveri, the traditional family based economic system does not help women on divorce because it is predicated on the traditional power structure within the home which is in favour of men. on divorce, women are invariably left high and dry# and with few alternatives than to return home to their parents or other extended family members for support.